Association of HLA-DRB1 and -DQ Alleles and Haplotypes with Type 1 Diabetes in Jordanians - Khdair, Sawsan I.; Jarrar, Wassan; Jarrar, Yazun B.; Bataineh, Safa'a; Al-Khaldi, Omar (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: The Human Leukocyte Antigen (HLA) class II genes, particularly the HLADR and -DQ loci, have been shown to play a crucial role in Type 1 Diabetes (T1D) development. Objective: This study is the first to examine the contribution of the HLA-DR/DQ alleles and haplotypes to T1D susceptibility in Jordanians. Methods: Polymerase chain reaction sequence-specific primers (PCR-SSP) were used to genotype 41 Jordanian healthy controls and 50 insulin-dependent diabetes mellitus (IDDM) patients. Results: The following alleles were found to be significant high risk alleles in T1D Jordanian patients: DRB1*04 (OR=3.95, p<0.001), DRB1*0301(OR=5.27, p<0.001), DQA1*0301 (OR=5.67, p<0.001), DQA1*0501(OR=3.18, p=0.002), DQB1*0201(OR=2.18, p=0.03), DQB1*0302 (OR=5.67, p<0.001). However, Jordanians harboring the DRB1*0701 (OR=0.37, p=0.01), DRB1*1101 (OR=0.2, p=0.01), DQA1*0505 (OR=0.31, p=0.02), DQA1*0103 (OR=0.33, p=0.04), DQA1*0201 (OR=0.45, p=0.04), DQB1*0301 (OR=0.23, p=0.001), DQB1*0501 (OR=0.18, p=0.009) alleles had a significantly lower risk of developing T1D. Conclusion: A strong positive association of DRB1*04-DQA1*0301-DQBl*0302 (OR=5.67, p<0.001) and DRB1*0301-DQA1*0501-DQB1*0201 (OR=6.24, p<0.001) putative haplotypes with IDDM was evident in Jordanian IDDM patients whereas DRB1*1101-DQA1*0505- DQB1*0301 (OR=0.23, p=0.03) was shown to have a protective role against T1D in Jordanians. Our findings show that specific HLA class II alleles and haplotypes are significantly associated with susceptibility to T1D in Jordanians.
Keywords: Insulin-dependent diabetes mellitus (IDDM)